Agrarian Law Enforcement and Settlement of Land Affairs Dispute in Judicature Process - , Supandi (International Conference of ASEAN Prespective and Policy (ICAP); Vol 1 No 1 (2018): INTERNATIONAL CONFERENCE OF ASEAN PERSPECTIVE AND POLICY (ICAP), 2018)
This dispute settlement option beyond the court had developed for other cases such as certain criminal cases in work force dispute or environmental or land affairs case, hence, solely, it was not applied to commercial cases only. Firstly, by filing accusation through reply. Secondly, it is determination stage from verification through judging. Thirdly, it is exercise state, i.e, judge implementation.  Any such stage requires long relative time, expensive and  complex. This research is a normative juridical research referring to the legal norms contained in the laws and regulations on Agrarian Law Enforcement And Settlement of Land Affairs Dispute In Judicature Process. Data obtained from normative juridical research is legal research using secondary data are official documents, books related to the object of research, research results in the form of reports, legislation and jurisprudence.Although any land affair dispute had occurred at any area, immediately, it may be solved by local officer and  its results may be received by parties in dispute. Lately, this condition my create law renewal on land affairs preceded by development of land affairs policy, of course, it should be commenced by law development of land affairs as part of national law system. Complexity of agrarian law enforcement  become serious problem, it is based on land function is very strategic to support activities of  economy, social, technology and information progress. Hence, common will and commitment  to seek out  land affair disputes  in Indonesia which had sacrificed so many people,  either  local government,  law enforcement apparatus, colleges and  all communities  should be striven for, and it should precede resolution by negotiation, and provided that it may not be achieved, it should be striven by mediation, and when it may not be achieved so, then, the court  is  last end/alternative to be achieved. Hence, judge’s award as Ultimatum remedies (last end) for land affair dispute and whomever should  realize Court’s rules which had had permanent legal power because its position as law in concrete case/matter.